1999
DOI: 10.1177/0021955x9903500205
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Properties of Conventional and Auxetic Foams. Part II: Shear

Abstract: Auxetic materials with a negative Poisson's ratio have the fascinating property of expanding laterally when stretched longitudinally. This property is fundamentally important to the properties of a material, and significant changes in the value of the ratio have important effects on mechanical performance. This paper examines the variation in static and dynamic shear moduli on a range of auxetic foams and also examines variation in loss tangent. It is shown that both the static, elastic shear modulus and the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Several experiments have therefore been performed to examine the properties of various foam specimens. 37,[40][41][42][43][44][45][46] Shortly aer Lakes's introduction, Friis et al (1988) studied transformed polymeric and metallic foams. 37 All foams were found to exhibit a negative Poisson's ratio and smaller elastic moduli as compared to the initial foaming material.…”
Section: Foamsmentioning
confidence: 99%
“…Several experiments have therefore been performed to examine the properties of various foam specimens. 37,[40][41][42][43][44][45][46] Shortly aer Lakes's introduction, Friis et al (1988) studied transformed polymeric and metallic foams. 37 All foams were found to exhibit a negative Poisson's ratio and smaller elastic moduli as compared to the initial foaming material.…”
Section: Foamsmentioning
confidence: 99%
“…Among others, a spectroscopic investigation of auxetic PTFE (polytetrafluoroethylene) is reported in [49], a holographic interferometry study of re-entrant, auxetic copper foam is described in [50], investigation of auxetic nematic structures in liquid crystals is reported in [51] and analysis of the material microstructure are presented in [52,53]. Experimental investigation of dynamic properties of foams and their dependence on temperature effects are reported in [54].…”
Section: Technological Experimental and Manufacturing Issuesmentioning
confidence: 99%
“…In dynamics several applications in shock and sound absorbing materials are possible (see also the micro-mechanical modelling reported in [72], the article [54] with experimental results of static and dynamic shear moduli and loss tangents, the experimental study of acoustic reflection in [85] and the study of vibrational characteristics in sandwich plates reported in [73]). Recent results in dynamics and multi-physics applications (electromagnetic or thermal effects) are reported in [75 -77, 86] and [87 -89], respectively.…”
Section: Existing and Potential Applicationsmentioning
confidence: 99%
“…He manipulated the Poisson ratio by compressing a polyester foam, heat treating it, and subsequently cooling it, to obtain foam which exhibited a negative Poisson ratio. Several others have produced and examined auxetic PU foams in a similar manner 16–25. Each material reported has been altered to obtain cells with so called re‐entrant15 or inverted structures, see Figure 2.…”
Section: Introductionmentioning
confidence: 99%